Advances in Imaging Studies for Assessing Epicardial Adipose Tissue - Yu ZHANG; Xiangling LIN; Pei NIE (CT Lilun yu yingyong yanjiu)
Epicardial adipose tissue (EAT) is situated adjacent to the myocardium and coronary arteries and closely associated with the occurrence and progression of various cardiovascular diseases, including coronary artery disease (CAD), atrial fibrillation (AFib), and heart failure (HF). Ultrasound, computed tomography (CT), magnetic resonance (MR), and artificial intelligence (AI) have enabled the quantitative assessment of EAT, thus aiding in the precision diagnosis and risk stratification of cardiovascular diseases. This review discusses the anatomy and physiological functions of EAT, its correlation with cardiovascular diseases, and current multimodality imaging research with the aim of providing references for further in-depth imaging and future clinical studies of EAT.